Modified polyether sulfone hollow fiber hemodialysis membrane and preparation method thereof

By adding polyvinylpyrrolidone and citric acid as modifiers to the core liquid of the polyethersulfone hollow fiber hemodialysis membrane, the problem of insufficient hydrophilicity and anticoagulation properties of the membrane is solved, the stable hydrophilicity and anticoagulation properties of the membrane are achieved, other properties of the membrane are maintained, and the production process is simplified.

CN119656898AActive Publication Date: 2025-03-21CHONGQING YUANZHONGYUAN BIOMATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411850761.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing polyethersulfone hollow fiber hemodialysis membrane has insufficient hydrophilicity and anticoagulation, resulting in problems such as thrombosis, reduced membrane flux and immune response.

Method used

Polyvinylpyrrolidone and citric acid are added to the core liquid as a modifier. Through the chemical force of hydrogen bonding and polymer chain winding, the modifier is firmly bonded to the inner surface of the polyether sulfone film, improving the hydrophilicity and anticoagulation of the film.

Benefits of technology

The long-lasting, stable hydrophilicity and anticoagulation properties of the modified polyethersulfone hollow fiber hemodialysis membrane are achieved, and the mechanical properties, chemical resistance and high temperature resistance of the membrane are maintained, and the production process is simplified to facilitate large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190516980000041
    Figure BDA0005190516980000041
  • Figure BDA0005190516980000051
    Figure BDA0005190516980000051
  • Figure BDA0005190516980000052
    Figure BDA0005190516980000052
Patent Text Reader

Abstract

The invention discloses a modified polyethersulfone hollow fiber hemodialysis membrane and a preparation method thereof, a main body part of the hemodialysis membrane is a polyethersulfone membrane, a modifier of the polyethersulfone membrane comprises polyvinylpyrrolidone and citric acid, and modifier molecules are combined on the inner surface of a hollow fiber membrane to form the hemodialysis membrane. According to the hemodialysis membrane disclosed by the invention, the polyvinylpyrrolidone and the citric acid which are added into the core liquid are used as modifiers, the hydrophilicity of the polyvinylpyrrolidone and the anticoagulant property of the citric acid are utilized, and a proton donating group on a citric acid molecule is respectively connected with carbonyl on the polyvinylpyrrolidone in the core liquid, so that the hemodialysis membrane is prepared. Oxygen atoms on a main chain of polyethersulfone in the spinning solution act to form hydrogen bonds, polyvinylpyrrolidone and citric acid are combined on the inner surface of the hollow fiber membrane, and meanwhile, polyvinylpyrrolidone and polyethersulfone molecular chains are wound to further fix the hollow fiber membrane, so that the hollow fiber membrane is prepared. The modified polyether sulfone hollow fiber hemodialysis membrane has lasting and stable hydrophilicity and anticoagulation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a modified polyethersulfone hollow fiber hemodialysis membrane and a preparation method thereof. Background Art

[0002] Hollow fiber hemodialysis membrane is a key component of blood purification consumables. The performance of the membrane directly affects the effectiveness and safety of dialysis. Dialysis membrane materials mainly include cellulose and polymer synthetic materials. Polymer synthetic membranes are usually prepared by non-solvent induced phase separation (NIPS) method. The main process is: prepare a homogeneous polymer solution of a certain composition (including polymer, solvent, additives), core liquid, coagulation bath, and then extrude the polymer solution through a spinning die (spinneret), and exchange with the core liquid and coagulation bath to change the thermodynamic state of the polymer solution, so that it undergoes phase separation from the homogeneous state and transforms into a three-dimensional macromolecular network gel structure, which is finally solidified into a membrane.

[0003] Polyethersulfone is widely used in the preparation of hollow fiber hemodialysis membranes due to its good film-forming properties, good mechanical properties, chemical resistance, high temperature resistance and other characteristics. It is the main polymer synthetic membrane. However, due to the hydrophobicity of the polyethersulfone material itself, it is very easy to trigger the coagulation waterfall when in contact with blood, causing thrombus formation on the surface of the dialysis membrane, which in turn leads to problems such as membrane pore blockage, significant attenuation of membrane flux, and reduced toxin clearance rate; and it will also trigger complement activation in the body, causing the hemodialysis membrane to be attacked by the human immune system. In clinical applications, heparin (unfractionated heparin or low molecular weight heparin) is usually injected to inhibit the formation of thrombus in the dialyzer. However, heparin is difficult to metabolize, which is not suitable for some patients with bleeding symptoms, and long-term injection of heparin can also lead to thrombocytopenia, hyperkalemia, osteoporosis, etc. Therefore, improving the hydrophilicity and anticoagulability of polyethersulfone membrane materials is the current development trend of hemodialysis.

[0004] At present, the hydrophilic and anticoagulant modification of polyethersulfone membranes is mainly carried out by physical modification or chemical modification methods, and specific functional groups or substances such as amino groups, carboxyl groups, sulfonic acid groups, heparin, citric acid, etc. are introduced to improve the hydrophilicity and anticoagulant properties of the membrane. For example, Chinese patent CN 105311974A takes polysulfone hemodialysis membrane as the modification target, first prepares a triblock copolymer containing polysulfone or polyethersulfone and acrylic acid by atom transfer radical polymerization, and then blends the copolymer with polysulfone, spins, and prepares a polysulfone hemodialysis membrane. Heparin is grafted onto the surface of the dialysis membrane using the carboxyl groups on the surface of the dialysis membrane to improve the hydrophilicity and anticoagulant properties of the dialysis membrane.

[0005] Some existing physical or chemical modification methods for polyethersulfone membranes have the problem that the modified groups or substances will gradually be lost during use, or have poor compatibility with the main material of the membrane, resulting in a decrease in the mechanical properties, chemical resistance, high temperature resistance and other properties of the modified hollow fiber hemodialysis membrane; for example, the hydrophilicity is improved by blending polyvinyl pyrrolidone (PVP) and polyethylene glycol (PEG), but since PVP and PEG are water-soluble polymers, they are easily precipitated during the preparation and use of the membrane, resulting in a weakening or loss of hydrophilicity; or some complex modification methods can maintain the hydrophilicity and anticoagulant properties for a long time, but there are problems such as complex processes, high costs, and difficulty in large-scale production, such as grafting hydrophilic anticoagulant groups or substances onto polysulfone materials by plasma, irradiation, photoinitiation and other methods. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of poor hydrophilicity and anticoagulant properties of existing polyethersulfone hollow fiber hemodialysis membranes, and to provide a modified polyethersulfone hollow fiber hemodialysis membrane with stable hydrophilicity and anticoagulant properties. The present invention adds a hydrophilic anticoagulant modifier to the core liquid, and during the phase exchange forming process of the hollow fiber membrane, the hydrophilic anticoagulant modifier is coated on the inner surface of the hollow fiber membrane. The hydrophilic anticoagulant modifier is firmly bonded to the inner surface of the polyethersulfone membrane through chemical forces such as hydrogen bonds and the entanglement of polymer chains, thereby providing stable hydrophilicity and anticoagulant properties.

[0007] In order to achieve its purpose, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a modified polyethersulfone hollow fiber hemodialysis membrane, wherein the main part of the hemodialysis membrane is a polyethersulfone membrane, and the modifier thereof includes polyvinyl pyrrolidone and citric acid, and the modifier molecules are bound to the inner surface of the hollow fiber membrane.

[0009] The inner diameter of the hollow fiber hemodialysis membrane is 150-350 μm, and the wall thickness is 50-100 μm.

[0010] The second aspect of the present invention provides a method for preparing the modified polyethersulfone hollow fiber hemodialysis membrane, comprising the following steps:

[0011] S1. preparing a spinning solution: by weight percentage, mixing 14% to 22% of polyethersulfone, 3% to 15% of a porogen, 0% to 7% of a non-solvent and 56% to 83% of an organic solvent, heating to fully dissolve, standing to degas, and obtaining a spinning solution;

[0012] S2, preparing the core liquid: taking the raw material components of the core liquid, mixing them, and fully dissolving them to obtain the core liquid; in terms of weight percentage, the core liquid comprises 1-10% polyvinyl pyrrolidone, 1%-10% citric acid, and the balance is water;

[0013] S3. Preparation of hollow fiber membrane: The spinning solution and core liquid are respectively transported to the spinneret for extrusion, and then enter the water bath for solidification and molding after the air process, and finally washed, dried and collected.

[0014] Preferably, in step S1, after the raw materials are mixed, they are heated at a temperature of 60 to 90° C. for 8 to 24 hours, and then allowed to stand for degassing for 12 to 24 hours to obtain a spinning solution;

[0015] In step S2, the raw material components of the core liquid are mixed and heated at 20-60° C. to fully dissolve to obtain the core liquid.

[0016] Preferably, the specific operation of step S3 is: the spinning liquid and the core liquid are respectively delivered to the spinneret for extrusion through a metering pump, and the speed of the metering pump is adjusted so that the spinning liquid flow rate is 7-13 ml / min, and the core liquid flow rate is 7.5-13.5 ml / min. After an air path of 1-60 cm, the spinning liquid enters a water bath at a temperature of 20-60°C for curing and forming, and then is driven by a roller with a linear speed of 10-40 m / min, and is successively cleaned in a water washing tank at 60-95°C, dried in an oven at 80-140°C, and finally collected on a winding wheel.

[0017] Further preferably, the specific operation of step S3 is: the spinning liquid and the core liquid are respectively delivered to the spinneret for extrusion through a metering pump, and the speed of the metering pump is adjusted so that the spinning liquid flow rate is 9.4-9.8 ml / min, and the core liquid flow rate is 9.8-10.2 ml / min. After passing through an air path of 40-50 cm, the spinning liquid enters a water bath at a temperature of 50-60°C for curing and forming, and then is driven by a roller with a linear speed of 10-40 m / min to pass through a water washing tank at 70-90°C for cleaning, and then dried in an oven at 100-140°C, and finally collected on a winding wheel.

[0018] Preferably, in step S1,

[0019] The porogen is a mixture of one or more of polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol in any proportion;

[0020] The non-solvent is a mixture of one or more of water, ethanol, isopropanol, and glycerol in any proportion;

[0021] The organic solvent is dimethylacetamide.

[0022] Further preferably, in step S1, the porogen is polyvinyl pyrrolidone; and the non-solvent is water.

[0023] Preferably, in step S1, the spinning solution comprises, by weight percentage, 14% to 20% of polyethersulfone, 5% to 15% of porogen, 1% to 7% of non-solvent and 64% to 75% of organic solvent;

[0024] In step S2, the core liquid comprises 2-10% polyvinyl pyrrolidone, 1%-10% citric acid, and the remainder is water, by weight percentage.

[0025] Further preferably, the spinning solution comprises 14% to 17% of polyethersulfone, 8% to 15% of porogen, 3% to 7% of non-solvent and 64% to 72% of organic solvent;

[0026] The weight percentage of polyvinyl pyrrolidone in the core liquid is 2-7%, the weight percentage of citric acid is 4-10%, and the balance is water.

[0027] The beneficial effects of the present invention are:

[0028] 1. The modified polyethersulfone hollow fiber hemodialysis membrane provided by the present invention has a main body composed of polyethersulfone, and polyvinylpyrrolidone and citric acid added to the core liquid are modifiers. The hydrophilicity of polyvinylpyrrolidone and the anticoagulant property of citric acid are utilized, and the proton-donating groups (such as -COOH and -OH) on the citric acid molecules react with the carbonyl groups on the polyvinylpyrrolidone in the core liquid and the oxygen atoms on the main chain of polyethersulfone in the spinning solution to form hydrogen bonds, so that polyvinylpyrrolidone and citric acid are combined on the inner surface of the hollow fiber membrane, and polyvinylpyrrolidone is further fixed by the entanglement of the molecular chains of polyethersulfone, so that the modified polyethersulfone hollow fiber hemodialysis membrane has durable and stable hydrophilicity and anticoagulant properties.

[0029] 2. The present invention mainly adds a modified substance into the core liquid and fixes it on the inner surface of the hollow fiber membrane. The main part of the hollow fiber membrane is still composed of polyethersulfone, thereby ensuring that the modified hollow fiber hemodialysis membrane has good mechanical properties, chemical resistance and high temperature resistance.

[0030] 3. The hydrophilic anticoagulant modifier used in the present invention is composed of polyvinyl pyrrolidone and citric acid, and the modification process is simple. At the same time, the preparation process of the present invention is the same as the existing polyethersulfone hollow fiber hemodialysis membrane production process, and there is no need to change the process route or add new machinery and equipment. It can be produced on the original production line, which is easy to achieve large-scale production and reduces costs. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.

[0032] The experimental methods in the following examples are conventional methods unless otherwise specified.

[0033] Example 1 Modified polyethersulfone hollow fiber hemodialysis membrane of the present invention

[0034] 1. Preparation of modified polyethersulfone hollow fiber hemodialysis membrane

[0035] The modified polyethersulfone hollow fiber hemodialysis membrane of the present invention is prepared according to the following method:

[0036] Step 1, preparing spinning solution: preparing spinning solution according to the weight percentage of each component in Table 1, heating at 80° C. for 10 h, and then standing and degassing for 20 h to obtain spinning solution;

[0037] Step 2, preparing the core liquid: preparing the core liquid according to the weight percentage of each component in Table 1, heating at 50°C to fully dissolve to obtain the core liquid;

[0038] Step 3, preparation of hollow fiber membrane: the spinning liquid and core liquid are respectively delivered to the spinneret for extrusion through a metering pump, and the speed of the metering pump is adjusted to make the spinning liquid flow rate 9.65ml / min and the core liquid flow rate 10.05ml / min. After a 40cm air path, it enters a water bath at a temperature of 50°C for curing and forming, and then is driven by a roller with a linear speed of 20m / min, and is successively cleaned in a water washing tank at 80°C, dried in an oven at 120°C, and finally collected on a winding wheel.

[0039] Table 1 Composition of spinning solution and core solution in each preparation example and comparative example

[0040]

[0041]

[0042] *Note: The values ​​in the table are the weight percentage of each component in the spinning solution or core solution.

[0043] 2. Performance testing:

[0044] The modified polyethersulfone hollow fiber hemodialysis membrane prepared in Table 1 was subjected to product performance testing in accordance with "YY / T 1920-2023 Dialyzer Blood Compatibility Test" and "GB / T32360-2015 Ultrafiltration Membrane Test Method".

[0045] The results are shown in Table 2.

[0046] Table 2 Performance comparison of the embodiments and comparative examples

[0047]

[0048] As shown in Table 2, compared with Comparative Example 1-2, by adding the modifier polyvinyl pyrrolidone + citric acid to the core liquid, the contact angle of the modified polyethersulfone hollow fiber hemodialysis membrane is reduced, and the pure water flux recovery rate is increased, indicating that the hydrophilicity of the membrane is improved; the APTT time is prolonged, indicating that the anticoagulant property of the membrane is improved; the pure water ultrafiltration rate results show that the hemodialysis membrane product meets the requirements of hemodialysis products. In summary, the product performance of Examples 1-3 is better overall.

[0049] Comparative Examples 3-4 use other modifier combinations, and the hydrophilicity and anticoagulant properties of the dialysis membrane are significantly worse than the combination of polyvinyl pyrrolidone + citric acid, and the comprehensive performance fails to be significantly improved. The present invention attempts a combination of multiple modifiers and different modifiers through preliminary experiments, such as glycerol, polyethylene glycol, etc., and attempts to add modifiers to the core liquid in order to fix the modifiers on the inner surface of the hollow fiber of the dialysis membrane to significantly improve the hydrophilicity and anticoagulant properties. Finally, it is determined to use a combination of polyvinyl pyrrolidone + citric acid, and both are added to the core liquid. The obtained dialysis membrane product can achieve the preset target, while maintaining a simple production process, which is convenient for large-scale production.

Claims

1. A modified polyethersulfone hollow fiber hemodialysis membrane, characterized in that: The main part of the hemodialysis membrane is a polyethersulfone membrane, and its modifier includes polyvinyl pyrrolidone and citric acid. The modifier molecules are combined with the inner surface of the hollow fiber membrane.

2. The modified polyethersulfone hollow fiber hemodialysis membrane according to claim 1, characterized in that: The inner diameter of the hollow fiber hemodialysis membrane is 150-350 μm, and the wall thickness is 50-100 μm.

3. The method for preparing the modified polyethersulfone hollow fiber hemodialysis membrane according to claim 1 or 2, characterized in that: The steps include: S1. preparing a spinning solution: by weight percentage, mixing 14% to 22% of polyethersulfone, 3% to 15% of a porogen, 0% to 7% of a non-solvent and 56% to 83% of an organic solvent, heating to fully dissolve, standing to degas, and obtaining a spinning solution; S2, preparing the core liquid: taking the raw material components of the core liquid, mixing them, and fully dissolving them to obtain the core liquid; The core liquid comprises, by weight percentage, 1 to 10% polyvinyl pyrrolidone, 1 to 10% citric acid, and the remainder is water; S3. Preparation of hollow fiber membrane: The spinning solution and core liquid are respectively transported to the spinneret for extrusion, and then enter the water bath for solidification and molding after the air process, and finally washed, dried and collected.

4. The preparation method according to claim 3, characterized in that: In step S1, the raw materials are mixed and heated at a temperature of 60 to 90° C. for 8 to 24 hours, and then allowed to stand for degassing for 12 to 24 hours to obtain a spinning solution; In step S2, the raw material components of the core liquid are mixed and heated at 20-60° C. to fully dissolve to obtain the core liquid.

5. The preparation method according to claim 3, characterized in that: The specific operation of step S3 is: the spinning liquid and the core liquid are respectively delivered to the spinneret for extrusion through a metering pump, and the speed of the metering pump is adjusted so that the spinning liquid flow rate is 7-13 ml / min and the core liquid flow rate is 7.5-13.5 ml / min. After passing through an air path of 1-60 cm, the spinning liquid enters a water bath at a temperature of 20-60°C for curing and forming, and then is driven by a roller with a linear speed of 10-40 m / min, and is successively cleaned in a water washing tank at 60-95°C, dried in an oven at 80-140°C, and finally collected on a winding wheel.

6. The preparation method according to claim 5, characterized in that: The specific operation of step S3 is: the spinning liquid and the core liquid are respectively delivered to the spinneret for extrusion through a metering pump, and the speed of the metering pump is adjusted to make the spinning liquid flow rate 9.4-9.8 ml / min, and the core liquid flow rate 9.8-10.2 ml / min. After passing through an air path of 40-50 cm, the spinning liquid enters a water bath at a temperature of 50-60°C for curing and forming, and then is driven by a roller with a linear speed of 10-40 m / min to pass through a water washing tank at 70-90°C for cleaning, and then dried in an oven at 100-140°C, and finally collected on a winding wheel.

7. The preparation method according to claim 3, characterized in that: In step S1, The porogen is a mixture of one or more of polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol in any proportion; The non-solvent is a mixture of one or more of water, ethanol, isopropanol, and glycerol in any proportion; The organic solvent is dimethylacetamide.

8. The preparation method according to claim 7, characterized in that: In step S1, the porogen is polyvinyl pyrrolidone; and the non-solvent is water.

9. The preparation method according to claim 7 or 8, characterized in that: In step S1, the spinning solution comprises, by weight percentage, 14% to 20% of polyethersulfone, 5% to 15% of a porogen, 1% to 7% of a non-solvent and 64% to 75% of an organic solvent; In step S2, the core liquid comprises 2-10% polyvinyl pyrrolidone, 1%-10% citric acid, and the remainder is water, by weight percentage.

10. The preparation method according to claim 9, characterized in that: The spinning solution comprises 14% to 17% of polyethersulfone, 8% to 15% of a porogen, 3% to 7% of a non-solvent and 64% to 72% of an organic solvent; The weight percentage of polyvinyl pyrrolidone in the core liquid is 2-7%, the weight percentage of citric acid is 4-10%, and the balance is water.

Citation Information

Patent Citations

  • Blood dialysis membrane with high blood coagulation resistance and preparation method therefor

    CN105311974A

  • Preparation method of anticoagulation hemodialysis membrane

    CN106466563A

  • Casting solution, ultrafiltration membrane, reverse osmosis composite membrane or nanofiltration composite membrane

    CN109173753A

  • Preparation method of hollow fiber hemodialysis membrane

    CN114504953A

  • Integral asymmetric membrane, method for producing said membrane and use thereof

    CN1917935A